PENGARUH KOMPETENSI JURU BAHASA ISYARAT PADA SIARAN BERITA CNN INDONESIA DI TRANS TV TERHADAP PEMENUHAN KEBUTUHAN KHALAYAK PENYANDANG TUNARUNGU (Survey Pada Komunitas Gerkatin Jakarta Pusat) - Sri Hastuti (2020)
THE INFLUENCE OF INTERPRETER GESTURE COMPETENCY ON CNN INDONESIA NEWS ON TRANS TV OF VIEWERS NEEDS DEAF (A SURVEY OF THE CENTRAL JAKARTA GERKATIN COMMUNITY) SRI HASTUTI ABSTRACT Interpreter gesture are used in news broadcasts as translators for the deaf. Sign Language Interpreters are used in news broadcasts as translators for the deaf. A Sign Language Interpreter must of course have the competence to be able to meet the needs of the audience well. One of the news broadcasts that uses Sign Language Interpreters is CNN Indonesia. This study aims to determine the magnitude of the influence of Sign Language Interpreter competence on the Indonesian CNN news broadcast on Trans TV Against the Meeting the Needs of People with Deaf (Central Jakarta Gerkatin Community Survey. Data analysis method used is quantitative analysis with validity and reliability test. The population in this study is a member of the Gerkatin Community of Central Jakarta with a sample determined by probability sampling and then using certain criteria such as the Indonesian CNN audience, can fill out a questionnaire and get 43 samples.The results of the study show that there is an influence of Sign Language Interpreter competence on CNN Indonesia news broadcasts on compliance audience needs for the deaf.Results of the correlation coefficient is r = 0.399 with this value included in the "low" relationship because it lies between 0.200-0.399. Analysis of the results of the regression test showed that the variable X did not change and the Y variable was 5.750 due to positive b, so the Y variable rose by 0.431. Analysis of the results of the coefficient of determination that is equal to 15,9%, it can be concluded that 15.9% fulfillment of audience needs is determined by the competence of Sign Language Interpreters. Hypothesis test results using a significance level of 5% obtained results of 2.802 with t table is 2.01954 based on these calculations, the results of the calculation of t count> t table is 2.802> 2.01954 then it can be concluded that H0 is rejected and Ha is accepted. Keywords: Competence, Deaf ,Interpreters Gesture, Viewers Needs.